2011
DOI: 10.1111/j.1439-0426.2010.01653.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of clove oil to anaesthetize larvae of Russian sturgeon (Acipenser gueldenstaedtii)

Abstract: The efficacy of clove oil as an anaesthetic was evaluated in larvae of Russian sturgeon (Acipenser gueldenstaedtii) using four anaesthetic concentrations varying from 0.20 to 0.75 g L )1 Mean length, 13.7 ± 0.70 mm, 44 larvae placed individually to the anaesthetic bath, and induction (I-1 and I-2) and recovery times (R-1 and R-2) recorded at 18.0 ± 0.01°C. Larvae failed to respond to external stimuli ‡3 min (3.19 min) and recovered in ‡5 min (5.10 min) at 0.20 g L )1 and at the other three doses larvae reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…We found a positive relationship between anesthetic concentration and recovery time in this study. Similar effects have been demonstrated in A. gueldenstaedtii (Akbulut et al, 2011), A. persicus (Adel et al, 2016), S. glanis (Gökçek et al, 2016) and C. auratus (Kizak et al, 2018). However, it was reported that similar or shorter recovery time in P. scalare (Mitjana et al, 2014), S. senegalensis (Weber et al, 2009), S. rivulatus (Ghanawi et al, 2013) exposed to clove oil, and C. macropomum (Saccol et al, 2017) exposed to M. sylvatica and C. longa essential oils.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…We found a positive relationship between anesthetic concentration and recovery time in this study. Similar effects have been demonstrated in A. gueldenstaedtii (Akbulut et al, 2011), A. persicus (Adel et al, 2016), S. glanis (Gökçek et al, 2016) and C. auratus (Kizak et al, 2018). However, it was reported that similar or shorter recovery time in P. scalare (Mitjana et al, 2014), S. senegalensis (Weber et al, 2009), S. rivulatus (Ghanawi et al, 2013) exposed to clove oil, and C. macropomum (Saccol et al, 2017) exposed to M. sylvatica and C. longa essential oils.…”
Section: Discussionsupporting
confidence: 64%
“…The relationship was also recorded between induction time and 2-phenoxyethanol concentration at water temperature of 15 °C (R 2 = 0.925) and at 25 °C (R 2 = 0.954) (Figure 1). Similarly, negative relationship between anesthetic agent concentrations and induction time of anesthesia were reported in D. labrax and S. aurata (Mylonas et al, 2005), S. senegalensis (Weber et al, 2009), Acipenser gueldenstaedtii (Akbulut et al, 2011), Siganus rivulatus (Ghanawi et al, 2013), P. scalare (Mitjana et al, 2014), A. persicus (Adel et al, 2016), S. glanis (Gökçek et al, 2016), Colossoma macropomum (Saccol et al, 2017), Carassius auratus (Kizak et al, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…There is considerable interest in testing clove oil as an anaesthetic agent to immobilize fish as an alternative to other anaesthetic agents that are more expensive and pose a potential hazard to the handler (Soto & Burhanuddin 1995;Keene et al 1998;Sladky et al 2001;Woody, Nelson & Ramstad 2002;Iversen et al 2003;Mylonas et al 2005;Weber et al 2009;Akbulut, Ç avdar, Ç akmak & Aksungur 2011). Studies on anaesthetic agents, including clove oil, on rabbitfish are rare to nonexistent.…”
Section: Resultsmentioning
confidence: 99%
“…There are plenty of studies available on the anaesthetic dosage of clove oil (Hikasa, et al, 1986;Woody et al, 2002;Woolsey et al, 2004;Akbulut et al, 2011aAkbulut et al, , 2011bFeng et al, 2011) and benzocaine (Oswald, 1978;Mattson and Riple, 1989;Gomes et al, 2001) for pelagic fish species which are regarded as seeing-feeding fish, but comparative studies concerning the optimal dose and the effects of anaesthesia on feed intake for sturgeon species which forage on the bottom by touch with barbells (smelling-feeding fish species) are limited. Soto and Burhanuddin (1995) did, however, observe most rabbitfish (Siganus lineatus) feeding a few hours after anaesthesia with clove oil, Prince and Powell (2000) reported that adult rainbow trout (Oncorhynchus mykiss) fed actively 1 week after anaesthesia with clove oil, Pirhonen and Schreck (2003) stated that steelhead trout (Oncorhynchus mykiss) ate relatively well 4 h after anaesthesia with MS-222, clove oil and CO 2 and Sorum and Damsgard (2004) considered that benzocaine anaesthesia had only a minor and insignificant effect on feed intake in Atlantic salmon (Salmo salar).…”
Section: Bilalmentioning
confidence: 99%